Current issues of company evaluation under fintech - E. A. Demyanova (Real Economics Publishing House, 2018)
The purpose of the current study was to form theoretical issues and practical recommendations on development of methodology evaluation for companies implementing modern financial technologies. The research was conducted based on methodology of systematic research, synthesis, abstract logic and scientific forecast, statistical methods and factor analysis methods, expert evaluation, real option method, explored fuzzy logic. Research resulted in discovery of such companies’ features that implement modern financial technology as evaluation objects, as well as exogenous and endogenous factors that impact the evaluation of the researched companies, and these factors’ classification offered; there were methodological recommendations developed on qualitative and quantitative ranking of specific indeterminacy; there were adaptations performed to discounted cash flows, real options, and ratio methods. The methodology developed was approbated based on domestic and foreign companies that provide consulting and evaluations services. As a result of its usage, a more precise evaluation was provided for the companies implementing modern financial technologies. A separate practical usage regarded the adopted method of discounting rate calculation based on the correction for specific fintech implementation risks and the developed mechanism of real options usage for additional company’s value that allows receiving a more accurate evaluation numbers. The classification manual of specific risks developed by the author is used by evaluation practitioners. The scientific issues and practical recommendations on improvement of the companies’ evaluation that were developed within the study are being used for teaching of “Evaluation and business value management” course in Financial University.